Peningkatan Kualitas Pelayanan Publik Pada Mal Pelayanan Publik Kabupaten Luwu - Bastian, Bastian (Indonesian Democracy Research Center, 2025)
This study aims to formulate strategies for improving the quality of public services at the Public Service Mall of Luwu Regency. The research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation at the Investment and One-Stop Integrated Service Office, which is responsible for managing the Public Service Mall. The findings reveal that efforts to enhance public service quality are carried out through five main strategies: (1) a core strategy that emphasizes employee performance and the availability of infrastructure, (2) a consequence strategy focusing on accountability and transparency through e-government and community feedback, (3) a customer strategy to ensure excellent services that meet public expectations, (4) a monitoring strategy utilizing the Community Satisfaction Index as the basis for evaluation, and (5) a cultural strategy that aligns service values and ethics with the social context of the community. These findings underscore the importance of integrating performance, accountability, public satisfaction, and local culture to achieve more responsive and higher-quality public services.